Comparing full immunisation status of children (0-23 months) between slums of Kampala City and the rural setting of Iganga District in Uganda: a cross-sectional study - Awa Jammeh; Michael Muhoozi; Asli Kulane; Dan Kajungu (BMC, 2023)
Abstract Background Immunisation remains the most cost-effective public health intervention in preventing morbidity and mortality due to Vaccine-Preventable Diseases (VPDs). The study aims to compare the differences in immunisation coverage amongst children aged 0 to 23 months living in slums of Kampala city and Iganga as rural districts in Uganda. Methods This study utilises data from a cross-sectional survey done in 2019 in the slums of Kampala City and the rural district of Iganga within the Health and Demographic Surveillance Site (HDSS). It included 1016 children aged 0-23 months and their parents. A logistic regression model was used to analyse the relationship between multiple independent variables and the binary dependent variables (fully immunised) using Stata statistical software. The measures of association were odds ratios reported with a corresponding 95% confidence interval. Results Out of the 1016 participants, 544 participants live in the rural area and 472 participants in the slums. Slums had 48.9% (n = 231) of fully immunised children whilst rural areas had 43.20% (n = 235). The multivariate analysis showed that children living in slums are more likely to be fully immunised as compared to their counterparts in rural areas (Odds ratio:1.456; p = 0.033; CI:1.030-2.058). Immunisation coverage for BCG (98.9%), Polio 0 (88.2%), Penta1 (92.7%), and Pneumo1 (89.8%) were high in both settlements. However, the dropout rate for subsequent vaccines was high 17%, 20% and 41% for Penta, pneumococcal and rota vaccines respectively. There was poor uptake of the new vaccines with slums having 73.4% and 47.9% coverage for pneumococcal and rota vaccines respectively and rural areas had 72.1% and 7.5% for pneumococcal and rota vaccines respectively. Conclusion The low full immunisation status in this study was attributed to the child's residence and the occupation of the parents. Lack of education and poor access to messages on immunisation (inadequate access to mass media) are other contributing factors. Educational messages on the importance of immunisation targeting these underserved populations will improve full immunisation coverage.